Blood Pressure and Arterial Load After Transcatheter Aortic Valve Replacement for Aortic Stenosis. (July 2017) - Lindman, Brian R.; Otto, Catherine M.; Douglas, Pamela S.; Hahn, Rebecca T.; Elmariah, Sammy; Weissman, Neil J.; Stewart, William J.; Ayele, Girma M.; Zhang, Feifan; Zajarias, Alan; Maniar, Hersh S.; Jilaihawi, Hasan; et al.
Abstract : Background—: After aortic valve replacement, left ventricular afterload is often characterized by the residual valve obstruction. Our objective was to determine whether higher systemic arterial afterload—as reflected in blood pressure, pulsatile and resistive load—is associated with adverse clinical outcomes after transcatheter aortic valve replacement (TAVR). Methods and Results—: Total, pulsatile, and resistive arterial load were measured in 2141 patients with severe aortic stenosis treated with TAVR in the PARTNER I trial (Placement of Aortic Transcatheter Valve) who had systolic blood pressure (SBP) and an echocardiogram obtained 30 days after TAVR. The primary end point was 30-day to 1-year all-cause mortality. Lower SBP at 30 days after TAVR was associated with higher mortality (20.0% for SBP 100–129 mm Hg versus 12.0% for SBP 130–170 mm Hg; P <0.001). This association remained significant after adjustment, was consistent across subgroups, and confirmed in sensitivity analyses. In adjusted models that included SBP, higher total and pulsatile arterial load were associated with increased mortality ( P <0.001 for all), but resistive load was not. Patients with low 30-day SBP and high pulsatile load had a 3-fold higher mortality than those with high 30-day SBP and low pulsatile load (26.1% versus 8.1%; hazard ratio, 3.62; 95% confidence interval, 2.36–5.55). Conclusions—: Even after relief of valve obstruction in patients with aortic stenosis, there is an independent association between post-TAVR blood pressure, systemic arterial load, and mortality. Blood pressure goals in patients with a history of aortic stenosis may need to be redefined. Increased pulsatile arterial load, rather than blood pressure, may be a target for adjunctive medical therapy to improve outcomes after TAVR. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00530894 Abstract : Supplemental Digital Content is available in the text.